Student Engagements in a Low-Literacy Culture Country – The Case of Indonesia - Setiono, Bambang; Rahmi, Mutia; Aditya, Putri; Hamidah, Rusyda; Indrawan, Umar (APPS Publications, 2022)
Education in the 21st century calls for more student-centered learning systems to promote innovation and creativity skills over compliance and conformity attitudes. Student active engagement is one main feature of a student-centered learning system. In a country with a low literacy rate, this study looked at the effects of teaching strategies and lecturers’ classroom behavior on student involvement. Can we introduce a student-centered learning system in this kind of country? Using a survey method, this study collected the perception of undergraduate students from various universities in Indonesia. Online survey was used to capture student perceptions on learnings methods, lectures behavior and student engagement. This study found that learning method and lecturers’ behavior influenced student engagement in the learning process. This study adds to the literature on learning experiences for students. We found ways to increase and improve student engagement in low literacy-ranking nations.